DOĞRUDAN YABANCI YATIRIMLARININ AR-GE HARCAMALARI ÜZERİNDEKİ ETKİSİ: G7 ÜLKELERİ ÖRNEĞİ - MAMMADLİ, Alibay; Rahimli, Etimad (TURAN : stratejik arastirmalar merkezi, 2025)
In this study, the answer to the question of whether Foreign Direct Investments (FDI) affects RD expenditures is sought. In the study, it is aimed to conduct Panel Data analysis in the G7 countries (Canada, France, Germany, Italy, Japan, England, USA) between 1996 and 2018. In the research, it was concluded that it is appropriate to analyze with the fixed effects model with the help of the Driscool-Kraay estimator. Based on the results of the model, the effect of FDI and Gross capital formation on RD expenditures is negative, while the effect of Gross Domestic Product, Human Capital Index and Trade Openness on RD expenditures is estimated positively. These variables are among the factors affecting the RD expenditures of the G7 countries. In the study, it was concluded that the investments made in the G7 countries negatively affect the RD expenditures because they are not suitable for the technology and development level of these countries.